Creative heritage: Overcoming tensions between innovation and tradition in the luxury industry. (27th April 2020) - Carvajal Pérez, Daniel; Le Masson, Pascal; Weil, Benoit; Araud, Axelle; Chaperon, Vincent
Abstract : "Marketing" and "design" teams often experience conflicts when cooperating on innovation projects. In luxury industries, these difficulties are exacerbated by a tension between innovation and tradition, which, in turn, causes a loss of originality and operational efficiency. Based on three case studies of a luxury champagne house, we provide evidence of the existence of a type of cognitive resource—a creative heritage —that can help marketing and design teams in luxury organizations manage these tensions, address destructive and creative tensions, and, hence, gain originality that is coherent with tradition and operational efficiency.